Efficacy of 0.01% atropine for myopia control in a randomized, placebo-controlled trial depends on baseline electroretinal response - Henry H. L. Chan; Kai Yip Choi; Alex L. K. Ng; Bonnie N. K. Choy; Jonathan Cheuk Hung Chan; Sonia S. H. Chan; Serena Z. C. Li; Wing Yan Yu (Scientific Reports, 2022)
Abstract This study aimed to evaluate the efficacy of 18-month 0.01% atropine in 61 myopic children (aged 7–10) and the relationship with central retinal response (by multifocal electroretinogram [mfERG]) in a double-masked randomized placebo-controlled clinical trial. Global-flash mfERG was measured at baseline, while cycloplegic spherical equivalent refraction (SER) and axial length (AL) were measured at baseline and at 6-month intervals. Annualized change in SER and AL were compared between atropine and control groups, and the relationships with baseline mfERG were evaluated. Changes in SER (−0.70 ± 0.39D vs. −0.66 ± 0.41D, p = 0.63) and AL (0.32 ± 0.16 mm vs. 0.30 ± 0.22 mm, p = 0.52) were similar in atropine and control groups. Interestingly, in the placebo group, mfERG amplitude was negatively correlated with axial elongation (Rp = −0.44, p = 0.03) as in our previous study. However, in the atropine group, an opposite trend was observed that axial elongation was positively correlated with mfERG amplitude (Ra = 0.37, p = 0.04). Annualized myopia progression demonstrated similar opposite effect between atropine and placebo groups but did not reach statistical significance. An ERG screening protocol may be warranted to identify suitable candidates to reduce the likelihood of an unfavorable treatment response by 0.01% atropine.